2009
DOI: 10.1248/cpb.57.694
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Binary and Ternary Copper(II) Complexes with 1,10-Phenanthroline, 2,2'-Bipyridyl and Some .ALPHA.-Amino Acids in Aqueous Medium

Abstract: Interactions of certain amino acids with some metal ions have significant consequences in biological systems. Metal ions can act as co-factors in the regulation of enzymatic reactions. Interactions of metal ions with amino acid side chains or with different organic complexes is also essential for many biological events. In this study, the stability constants of 1 : 1 : 1 ternary complexes of Cu(II) with 1,10-phenanthroline (Phen) as the primary ligand, and 2,2'-bipyridyl (Bpy) and some selected alpha-amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In some systems (Cu–GA–G, Cu–GA–GG, Cu–GA–GGG, Ni–GA–G, and Cu–FA–G), Δ log K are negative. These negative values may be the result of the high stability of their binary complexes, reduction in the coordination sites of the metal ions, steric hindrance, and electrostatic effect. For the FA-GG and FA-GGG systems, Δ log K values have a similar tendency as their corresponding binary complexes. It may occur due to the competition between ligands since FA, GG, and GGG show almost similar chelating abilities toward metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…In some systems (Cu–GA–G, Cu–GA–GG, Cu–GA–GGG, Ni–GA–G, and Cu–FA–G), Δ log K are negative. These negative values may be the result of the high stability of their binary complexes, reduction in the coordination sites of the metal ions, steric hindrance, and electrostatic effect. For the FA-GG and FA-GGG systems, Δ log K values have a similar tendency as their corresponding binary complexes. It may occur due to the competition between ligands since FA, GG, and GGG show almost similar chelating abilities toward metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…The higher stability of the L1 complexes with Cu 2+ and Zn 2+ cannot be ascribed to the different coordination abilities of bpy and phen. In fact, phen is a better chelating agent than bpy and, for instance, the stability constants of the [Cu L ] 2+ complex are 9.1 and 8.08 log unit with L =phen and bpy, respectively …”
Section: Resultsmentioning
confidence: 99%
“…Binding modes at different pH-values of ternary coordination compounds were investigated with different amino acids and heterocyclic bases, including l -threonine and 1,10-phenanthroline [ 24 , 25 ]. It was shown that ternary coordination species [Cu(aa)(N–N)] + (aa = aminoacidate; N–N = 2,2′-bipyridine or 1,10-phenanthroline) are more stable than either [Cu(aa) 2 ] or [Cu(N–N) 2 ] 2+ binary compounds [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%